Ecological Skills developed by social networks Visit.Margarita account on Instagram - Ramírez Franco, María Mercedes (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2023)
The present work has been elaborated as an inspiration for the doctoral thesis called: Socio-emotional competencies and the Culture of Sensitivity in the university education. This investigation has been based on conducting research on the Instagram account Visit.Margarita and without persuasive power to develop ecological competencies. Trough the above, the qualitative paradigm and the hermeneutic phenomenological method have been used, analyzing the images, vídeos and opinions of the followers and their impact on the development of ecological competencies. Finally, to analyze images and vídeos, atlasti.9 was used, in order to provide added value to research.